Learning to love trade again: Time to think small - Frank Lavin; Oscar Guinea (European Centre for International Political Economy (ECIPE), 2020)
We are at the moment, the first in seventy-five years, where there is no international consensus in support of trade. Indeed, trade is unloved, unsupported, and even unwanted. There is no shortage of topics in the rhetoric of trade complaints: from the rapid rise of China to Coronavirus as a metaphor for the evils of greater connectivity. Regardless of the validity of these complaints, none of them negate the central truth of trade: countries that engage in trade move ahead, and those that do not, stagnate. Our political leaders disagree. Anti-trade positions are held by leaders across the political spectrum, from Donald Trump to Bernie Sanders. And yet, the public is increasingly warm to the idea of trade. When Gallup asks Americans, "Do you see foreign trade more as an opportunity for economic growth through increased U.S. exports or a threat to the economy from foreign imports?" a record high of 79% see trade as an opportunity, with 18% viewing it as a threat. How did the world arrive at this moment where the benefits of trade are clearly evidenced while trade has become politically toxic? We identify four main factors: (i) U.S. absenteeism from the leadership role; (ii) detachment between trade and security architecture; (iii) no alternative leadership in Europe or elsewhere; and (iv) the cumbersome WTO process. Against this background we put forward five initiatives that will be big enough to count but unobjectionable enough to be adopted.
Keywords: 330; Handel; Außenwirtschaftspolitik; Welt